Great Depression and the New Deal.
Pranav Gupta and Jonathan Lee present information on the Great Depression of the 1930s and the New Deal of 1933 to 1938 in the United States. The authors provide definitions of key terms and highlight the causes and problems of the Great Depression, the philosophies of President Herbert Hoover and President Franklin D. Roosevelt, and the successes and failures of Roosevelt's New Deal programs. The causes of the Great Depression include the stock market crash of 1929, an unstable economy, and speculation on the financial markets.